Penetapan Kadar Migrasi Melamin dalam Peralatan Makan yang Beredar di Kota Banjarmasin dengan Metode Kromatografi Cair Kinerja Tinggi - Juraidah, Juraidah; Utama, Qabul Dinanta (Jurnal Teknologi dan Mutu Pangan, 2023)
Tableware and drinking utensils made of melamine have several advantages over utensils made of glass, ceramic or metal. Melamine is stronger, cheaper, attractive in design, lightweight and not easily broken. Although it has low toxicity, long-term exposure to melamine migratory has negative effects on health, especially on the kidneys because it can form insoluble crystals in combination with cinuric acid which causes the formation of kidney stones, especially in infants and children. This study aims to determine the migration of melamine and melamine levels in melamine cutlery using High Performance Liquid Chromatography (HPLC) method. The results of this study indicate that there has been migration from melamine cutlery. Temperature and type of simulants affect migration and levels of extracted melamine from melamine tableware. Simulans are media used as food substitutes in migration tests. By using a 3% acetic acid simulant and a simulant temperature of 66℃, the extracted melamine content ranges from 2.45 ppm to 8.14 ppm, but still meets the requirements, namely below 30 ppm. People should use melamine cutlery marked with food grade, not use melamine cutlery for foods with high temperatures and foods that are acidic, because this can cause melamine to migrate from the cutlery into the food.